Development of Standards for Presenting and Reporting clinical InterveNtions Televisually (SPRINT) reporting guidelines: A study protocol - Michael G. Fadel; Henry Douglas Robb; Bibek Das; Ayda Alizadeh; Aksaan Arif; Olivia Ariarasa; Matyas Fehervari; Hutan Ashrafian (PLoS ONE, 2026)
Background Videos of clinical intervention (VoCI) demonstrate medical and surgical approaches, including laparoscopy and robotics, endoscopy and interventional techniques. VoCI allow viewers to easily understand the steps of a specific procedure, enhancing clinical training through the acquisition of key perceptual and cognitive skills. However, there can be heterogeneity in video reporting, leading to the omission of critical procedural steps and suboptimal visual quality. This protocol describes the development of Standards for Presenting and Reporting clinical InterveNtions Televisually (SPRINT) guidelines through a Delphi process, which will provide a set of minimum items that should be reported by clinicians when uploading VoCI to improve their consistency and completeness. Methods and analysis The development of SPRINT reporting guidelines will follow five key steps. In step 1, a Steering Committee has been established to lead and coordinate the consensus development process. In step 2, a scoping review of current VoCI has been performed to generate preliminary checklist items. In step 3, a diverse international panel of clinical experts, trainees, educationalists, media platform providers and patient representatives will participate in a Delphi process, seeking ≥ 70% agreement on checklist items. In step 4, the SPRINT reporting guidelines will be finalised, along with an explanation and elaboration (E&E) document. In step 5, the guidelines will be broadly disseminated to ensure effective implementation. Registration details The project is pre-registered within the Open Science Framework ( https://osf.io/an2jt/ ) and the Enhancing the QUAlity and Transparency Of health Research (EQUATOR) Network.